Transformational Digital Leadership in Parenting: Child Empowerment and Digital Addiction Management: Kepimpinan Digital Transformasional Dalam Keibubapaan: Pemerkasaan Kanak-Kanak Dan Pengurusan Ketagihan Digital - Isa, Khairunesa; Palpanadan, Sarala Thulasi; Kadir, Zahuren Abdul; Shahlal, Syamimi Afiqah; Wan Muda, Wan Hani (Journal of Human Capital Development (JHCD), 2025)
This study examined the role of transformational digital leadership in the context of modern parenting with a focus on child empowerment strategies and digital addiction risk management. Qualitative data were obtained through roundtable discussions involving parents from diverse socioeconomic backgrounds, and analyzed using a thematic approach. Findings indicated that modeling positive digital behavior, granting controlled autonomy, and setting clear digital boundaries were core to family digital well-being. This study fills a literature gap by integrating transformational leadership theory into the dynamics of digital parenting, which is typically only addressed through a screen time control approach. The findings also highlight the need for digital leadership training for caregivers, collaboration with policymakers and educators, and the development of sustainable and ethical child-friendly digital ecosystems. The implications of the study align with Sustainable Development Goal (SDG) 3, which is to promote family health and well-being in the digital age.